Embodied Reflexivity: Positioning Embodiment in Disability Studies Research - Mohler, Elizabeth (Critical Disability Discourses, 2025)
This paper presents an analysis of embodied reflexivity, positioning embodiment in disability research. The overarching aims of this research are first to critically outline the key/guiding tenets of embodied reflexivity to locate its theoretical groundings. Second, the research critically assesses how embodied reflexivity has been taken up in Disability Studies (DS). Third, it determines if and how the practice of embodied reflexivity is experienced differently by scholars with and without disabilities within the context of DS research. Fourth, it illustrates the methodological implications of embodied reflexivity for scholars with a disability and determines the methodological value of embodied reflexivity for disability-related research. This paper concludes with a summary of key findings and implications for future research. Keywords: Embodied reflexivity; Embodiment; Disability; Disability studies; Reflexive embodied empathy